Peruvian Street Lives : Culture, Power, and Economy among Market Women of Cuzco - Seligmann, Linda J., 1954- (Book collections on Project MUSE., 2004)
"For more than twenty years Linda J. Seligmann has walked the streets of Peru in city and countryside alike, talking to the women who work in the informal and open-air markets of the Andean highlands of Cuzco. In this readable ethnography, composed of vignettes and accompanied by a superb series of photographs, Selignmann offers a humane yet incisive portrayal of their lives. In Peruvian Street Lives, Seligmann leads us through the complex, informal networks that market women have established. Despite how disorderly and chaotic these networks appear, she argues that they often paradoxically keep dysfunctional economies and corrupt bureaucracies from utterly destroying the ability of citizens to survive from day to day. Seligmann asks why the constructive efforts of market women to make a living provoke such negative social perceptions from some members of Peruvian society, who see them as symbols and actual catalysts of social disorder, domestically and publicly. The book traces the impact on market women and market activities of distant yet enormously powerful forces, such as economic globalization. At the same time it shows how market women eke out a living, combat discrimination, and creatively transgress existing racial and gender ideologies, within the rich and expressive cultural traditions they have developed."--Back cover.